Karsinoma Sel Skuamosa Paru Kanan Dengan PPOK Dan Atelektasis Paru Kiri - Nurul Muna; Indra Buana (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Lung cancer is one of the most common causes of death today. One case of right lung squamous cell carcinoma with COPD and atelectasis has been reported in a 44 year old male patient. Based on the history, the patient said he had experienced chest pain for 1 week before entering the hospital and had a cough without phlegm or blood. Physical examination revealed dull chest wall percussion at the apex of the right lung and dullness in the left lung field, vesicular breathing sounds in both lung fields and rhonchi in the left lung field. The results of the supporting examination found a mass in the left lung on a chest x-ray and a bronchoscopy examination found a right lung tumor (type?) T3N1M0 Stage IIIA and the results of the anatomical pathology examination showed a picture of non-small cell carcinoma type squamous cell carcinoma. Patients are treated with chemotherapy and symptomatic therapy.